STRENGTHENING RELIGIOUS LITERACY TO MINIMIZE FORMS OF BULLYING IN EARLY CHILDREN - Maruti, Endang Sri; Hanif, Muhammad (Proceeding International Seminar of Islamic Studies, 2024)
Early childhood is in a critical phase of development, where they not only experience physical growth but also social, emotional and spiritual development. Threats to children's safety, such as bullying, are an important issue in this context. Bullying, both physical and psychological, is an increasingly prominent problem. The high number of cyber bullying cases in Indonesia is an interesting thing to discuss. The aim of this research is to discuss approaches to strengthening religious literacy as an effort to minimize forms of bullying in early childhood. This research method is qualitative with a descriptive perspective. The results of this research state that religious literacy is not only an understanding of religious teachings, but also includes moral values, ethics and behavioral norms. Understanding religious moral values helps children develop strong character and understand human principles. By building a strong moral and spiritual foundation from an early age, children can grow into individuals who are empathetic, tolerant, and able to fight against all forms of injustice. This approach not only creates a safe environment for children but also builds the foundation for a more harmonious and civilized society.